Strategi Pencegahan dan Deteksi Dini Stunting di Desa Karangmuncang - Julaeha, Laela; Heriyana, Tio; Nafisa, Ira; Andini, Anisa Sakina; Elpiani, Mulya (Jurnal Pengabdian Tri Bhakti, 2024)
Stunting refers to a condition in children characterized by growth disturbances, resulting in height that is inconsistent with their age. This issue arises from chronic nutritional deficiencies, particularly prolonged malnutrition during the first 1,000 days of life (HPK). This condition is marked by stunted growth caused by nutritional and health problems occurring before and after birth. The activities took place over 46 days in one of the villages located in the Cigandamekar sub-district of Kuningan Regency, namely Karangmuncang Village. The aim of this service is to educate about the risks, prevention strategies, and early detection of stunting. Activities in Karangmuncang Village were carried out with a structured approach that included planning, implementation, and reporting of follow-up results. Among the activities conducted was an educational seminar focused on stunting, which included counseling on nutrition and daily family practices. Additionally, the Healthy Kitchen Program to Address Stunting (DASHAT) was implemented in collaboration with Posyandu cadres, targeting pregnant and breastfeeding mothers as well as parents of toddlers. Furthermore, this service also involved recording meal menus and monitoring the growth of children at risk of stunting over a period of 30 days. Keywords: Stunting, Nutrition, DASHAT, Karangmuncang